Advanced technologies for studying circulating tumor cells at the protein level. (December 2013) - Chan, Charles Ming Lok; Au, Thomas Chi Chuen; Chan, Anthony Tak Cheung; Ma, Brigette Buig Yue; Tsui, Nancy Bo Yin; Ng, Simon Siu Man; Hui, Edwin Pun; Chan, Lawrence Wing Chi; Ho, Wing Shan; Yung, Benjamin Yat Ming; Wong, Sze Chuen Cesar
Metastasis is the main cause of cancer death. As the tumor progresses, cells from the primary tumor site are shed into the bloodstream as circulating tumor cells (CTCs). Eventually, these cells colonize other organs and form distant metastases. It is therefore imperative that we gain a better understanding of the biological characteristics of CTCs for development of novel treatment modalities to minimize metastasis-associated cancer deaths. In recent years, rapid developments in technologies for the study of CTCs have taken place. We now have a variety of tools for the isolation and examination of CTCs which were not available before. This review introduces some commonly used protein markers in CTC investigations and summarizes a few advanced technologies which have been successfully applied for studying CTC biology at the protein level.